Knitting, Weaving: To Think the Cultural Construction - Pizarro-Romero, A (UNIV NAC COLOMBIA, SEDE AMAZONIA, 2018)
The scholarship cultural interactions in Latin America and its recent history: a critical perspective and a proposal. The multiplicity of cultural flows as well as the internal movement in them between the different literary systems conduct us to think a system of relations where many cultural contributions interfere at the same time or in sequence, in a specific time scale for each situation, where the crossroads can consolidate or not, where each flow has at the time a different energy from the historic contextand that is why there are hegemonic and subaltern ones. It can be seen as knitting, a weave, in constant movement.